Asymptomatic Plasmodium falciparum carriage at the end of the dry season is associated with subsequent infection and clinical malaria in Eastern Gambia - Balotin Fogang; Lionel Lellouche; Sukai Ceesay; Sainabou Drammeh; Fatou K. Jaiteh; Marc-Antoine Guery; Jordi Landier; Cynthia P. Haanappel; Janeri Froberg; David Conway; Umberto D’Alessandro; Teun Bousema; et al. (Malaria Journal, 2024)
Abstract Background Chronic carriage of asymptomatic low-density Plasmodium falciparum parasitaemia in the dry season may support maintenance of acquired immunity that protects against clinical malaria. However, the relationship between chronic low-density infections and subsequent risk of clinical malaria episodes remains unclear. Methods In a 2-years study (December 2014 to December 2016) in eastern Gambia, nine cross-sectional surveys using molecular parasite detection were performed in the dry and wet season. During the 2016 malaria transmission season, passive case detection identified episodes of clinical malaria. Results Among the 5256 samples collected, 444 (8.4%) were positive for P. falciparum. A multivariate model identified village of residence, male sex, age ≥ 5 years old, anaemia, and fever as independent factors associated with P. falciparum parasite carriage. Infections did not cluster over time within the same households or recurred among neighbouring households. Asymptomatic parasite carriage at the end of dry season was associated with a higher risk of infection (Hazard Ratio, HR = 3.0, p < 0.0001) and clinical malaria (HR = 1.561, p = 0.057) during the following transmission season. Age and village of residence were additional predictors of infection and clinical malaria during the transmission season. Conclusion Chronic parasite carriage during the dry season is associated with an increased risk of malaria infection and clinical malaria. It is unclear whether this is due to environmental exposure or to other factors.